Let $k$ be an algebraically closed field. Let $I$ be the map that takes algebraic sets in $k^n$ to the ideal generated by them: $I : \{$ algebraic sets $\} \to \{$ ideals of $k[x_1,\dots, x_n] \}$, $I(X) = \{ f \in k[x_1, \dots, x_n] : f(X) = \{0\}\}$. Similarly let $Z$ be the map that takes ideals in $k[x_1,\dots, x_n]$ to algebraic sets. Then $I(Z(I)) = \sqrt{I}$.

How does that follow from Hilbert's Nullstellensatz?

This version of Nullstellensatz: If $k$ is an algebraically closed field then, the maximal ideals of $k[x_1,\dots, x_n]$ are of the form $(x_1 - a_1, \dots, x_n - a_n)$ where $a = (a_1, \dots, a_n)$ is a point in $k^n$.

  • $\begingroup$ This cannot be answered properly unless you give some formulation of the Nullstellensatz. For instance, one way to state it is to say precisely that $I(Z(I))= \sqrt{I}$ for any ideal $I$. Another way is for example that in a finitely generated $k$-algebra, every prime ideal is the intersection of all maximal ideals containing it. $\endgroup$ – Pavel Čoupek Dec 8 '13 at 20:03
  • 1
    $\begingroup$ This is Hilbert's Nullstellensatz as I know it. $\endgroup$ – egreg Dec 8 '13 at 20:03
  • $\begingroup$ Teh noes. I mean the version that says that over an algebraically closed field $k$, the maximal ideals in $k[x_1, \dots, x_n]$ are in bijective correspondence with points of $k^n$ and are given by the form $\hat{m} = (x_1 - a_1, \dots, x_n - a_n)$ for the corresponding point $a = (a_1, \dots, a_n) \in k^n$. $\endgroup$ – BananaCats Category Theory App Dec 8 '13 at 20:06
  • 2
    $\begingroup$ You have to use Rabinowitsch trick, you can find a proof in almost any commutative algebra textbook, see for instance Zariski's book volume 1. $\endgroup$ – user40276 Dec 8 '13 at 20:41
  • 1
    $\begingroup$ @EnjoysMath Sorry, but I'm not here for points, I'm here because I like math. $\endgroup$ – user40276 Dec 8 '13 at 20:45

Let $I$ be an ideal of $k[x_1, \dots, x_n]$. It is easy to see that $\sqrt{I}\subseteq IZ(I)$ ($f^l \in I$ implies $f^l(P)=0$ for every $P \in Z(I)$, which implies $f(P)=0$ for every $P \in Z(I)$ ).

The other inclusion is a bit more tricky. Assume that $ f \in IZ(I)$ and take some generators $f_1, f_2, \dots, f_k$ of $I$. Then the set $Z(\{f_1, f_2, \dots, f_k,x_{n+1}f-1\})$ is empty, since $f(P)=0$ whenever $f_1(P)=f_2(P)=\dots =f_k(P)=0$ (note that here we operate "one dimension higher", i.e. in $k^{n+1}$; $x_{n+1}$ is a new indeterminate). Hence $$J:=(f_1, f_2, \dots, f_k,x_{n+1}f-1)=k[x_1,\dots , x_n,x_{n+1}]$$ (if $J$ were a proper ideal, it would be contained in some maximal ideal $m$, but $Z(m)$ is a point, hence nonempty, and $Z(m)\subseteq Z(J)$). Therefore, one can write $$1=\sum_{i=1}^{k}f_i(x_1, \dots x_{n})h_i(x_1, \dots x_n,x_{n+1})+(x_{n+1}f(x_1, \dots x_{n})-1)h(x_1, \dots x_n,x_{n+1})$$

by using the substitution $x_{n+1}=\frac{1}{f}$ (formally, using an evaluation homomorphism), one has (in the localisation $k[x_1, \dots x_n]_f$)

$$1=\sum_{i=1}^{k}f_i(x_1, \dots x_{n})h_i(x_1, \dots x_n,\frac{1}{f})+(\frac{1}{f}f(x_1, \dots x_{n})-1)h(x_1, \dots x_n,\frac{1}{f}),$$ but the last term clearly vanishes, so $$1=\sum_{i=1}^{k}f_i(x_1, \dots x_{n})h_i(x_1, \dots x_n,\frac{1}{f}).$$

One can then easily see that the terms $h_i(x_1, \dots x_n,\frac{1}{f})$ are of the form $\frac{g_i}{f^{m_i}}$, where $g_i$ are polynomials in indeterminates $x_1, \dots, x_n$. Take $M:=\max_i m_i$. Then $$f^M=\sum_{i=1}^{k}f_ig_if^{M-m_i},$$ which is an equality in $k[x_1, \dots x_n]$. Hence, $f \in \sqrt{(f_1, \dots, f_k)}=\sqrt{I}$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.